2003
DOI: 10.1017/s0022029902005952
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in rennet-coagulated Spanish hard cheeses made from milk preserved by refrigeration and addition of carbon dioxide

Abstract: On-farm refrigeration of milk reduces the growth rate of mesophilic bacteria so allowing longer storage time of raw milk before processing. However, refrigeration creates a selective pressure favouring the multiplication of psychrotrophic bacteria present as normal contaminants in raw milk. Psychrotrophs are killed by most of the currently employed pasteurization and sterilization treatments of milk but they can produce extracellular heat-stable proteinases and lipases, which are capable of degrading various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…They observed that when compared with cheese made from pasteurised milk, CO 2 ‐treated milk exhibited slower initial growth of lactobacilli with lower levels of acid production. In follow up of this study, Ruas‐Madiedo et al. (2003) evaluated the effects of these treatments on proteolysis occurring in cheese and concluded that cheeses manufactured from CO 2 ‐treated milk showed lower levels of hydrophilic peptides while no variation in hydrophobic peptides amounts at the end of the ripening process.…”
Section: Preservation Of Dairy Products By Co2 Additionmentioning
confidence: 99%
“…They observed that when compared with cheese made from pasteurised milk, CO 2 ‐treated milk exhibited slower initial growth of lactobacilli with lower levels of acid production. In follow up of this study, Ruas‐Madiedo et al. (2003) evaluated the effects of these treatments on proteolysis occurring in cheese and concluded that cheeses manufactured from CO 2 ‐treated milk showed lower levels of hydrophilic peptides while no variation in hydrophobic peptides amounts at the end of the ripening process.…”
Section: Preservation Of Dairy Products By Co2 Additionmentioning
confidence: 99%
“…Compared to cheeses made from unpasteurized milk, both CO 2 ‐treated cheeses exhibited no change in volatile compound production, a reduction in clotting time, a higher cheese yield, and an increase in cheese hardness. In a later study (Ruas‐Madiedo and others 2003) the group extended this work by examining the effects of the treatments on proteolysis. Cheeses made from CO 2 ‐treated milk exhibited lower amounts of hydrophilic peptides and no change in hydrophobic peptides at the end of ripening.…”
mentioning
confidence: 99%
“…Of the several reported experiments using CO 2 as an acidulent prior to cheese manufacture, most have focused on the antimicrobial and coagulation firming effects of CO 2 (Calvo et al, 1993;McCarney et al, 1995;Ruas-Madiedo et al, 2003). Others have reported the effects of CO 2 on Cheddar cheese yield (McCarney et al, 1995;St-Gelais et al, 1997).…”
Section: Introductionmentioning
confidence: 99%